1992
DOI: 10.1136/jech.46.3.203
|View full text |Cite
|
Sign up to set email alerts
|

Maternal recall of infant feeding events is accurate.

Abstract: Study objective-Retrospective infant feeding data are important to the study of child and adult health patterns. The accuracy of maternal recall of past infant feeding events was examined and specifically the infant's age when breast feeding was stopped and formula feeding and solid foods were introduced.Design and setting-The sample consisted of Bedouin Arab women (n = 318) living in the Negev in Israel who were a part of a larger cohort participating in a prospective study of infant health and who were deliv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
79
3
2

Year Published

1994
1994
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 16 publications
1
79
3
2
Order By: Relevance
“…Although the studied population had a high level of schooling, and although a number of studies show evidence of reasonable accuracy for information provided by mothers regarding the length for which their children were breastfed, 6,8,10 it is possible that this information was not sufficiently precise in the present study. Such lack of precision would tend to obscure eventual associations between duration of breastfeeding and school-age obesity, driving the odds ratios towards the unit.…”
Section: Discussioncontrasting
confidence: 43%
“…Although the studied population had a high level of schooling, and although a number of studies show evidence of reasonable accuracy for information provided by mothers regarding the length for which their children were breastfed, 6,8,10 it is possible that this information was not sufficiently precise in the present study. Such lack of precision would tend to obscure eventual associations between duration of breastfeeding and school-age obesity, driving the odds ratios towards the unit.…”
Section: Discussioncontrasting
confidence: 43%
“…Previous studies have investigated the reliability of maternal reports on prenatal, perinatal and on postnatal factors, and suggest that maternal recall data are reproducible for perinatal factors, for example, birth weight, gestational age or medical procedures. 8,9 In contrast, maternal reports on prenatal factors, for example, maternal weight gain during pregnancy, 10 and early infant nutrition, for example, breastfeeding or introduction of solid food, 11,12 showed only moderate agreement or inconsistency in their reliability.…”
Section: Introductionmentioning
confidence: 90%
“…11,13 Generally, a shorter time span is associated with a higher repeatability of selfreports. The aim of this paper is to assess the repeatability of maternal reports of questions on prenatal, perinatal and early postnatal factors assessed by the PQ.…”
Section: Introductionmentioning
confidence: 99%
“…In general, breastfeeding history has been shown to be accurate and reliable. 29,30 However, Promislow et al examined maternal recall of breastfeeding duration by elderly women and reported significant misclassification in breastfeeding duration recalled 34 to 50 years after child birth; their finding demonstrated that misclassification would appreciably attenuate the true strength of association between breastfeeding and later health event under study. 31 Thus, even if there is misclassification for length of (or exclusivity of) breastfeeding, the true association between breastfeeding duration and triple-negative BC would be stronger than observed in this study.…”
mentioning
confidence: 99%